Genetic variability, heritability, genetic advance and character association of Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
An investigation was undertaken to study the Genetic variability, heritability, genetic advance and character association of Indian mustard (Brassica juncea L.) of twelve characters namely days to 50% flowering, days to maturity, plant height (cm), no. of primary branches per plant, no. of secondary branches per plant, no. of siliquae per plant, no. of seeds per siliqua ,1000- seed weight (g), biological yield per plant (g), harvest index (%), oil content (%) , seed yield per plant (g) in seven Indian mustard germplasm lines. The experiment material was evaluated in a randomized complete block design with three replications. Analysis of variance estimates of all the characters were found highly significant. Coefficient of variation for GCV and PCV were found high for the following traits i.e. primary branches per plant, 1000- seed weight (g), no. of seeds per siliqua and seed yield per plant. All the characters showing higher heritability except biological yield per plant (g). no. of siliquae per plant show higher genetic advance. Correlation study revealed that that seed yield had significant and positive association with no. of siliqua per plant (0.21G & 0.19P), number of Seeds per siliqua (0.35G & 0.13P),1000 seed weight (0.52G&0.45P), harvest index (0.79G & 0.78P) biological yield (0.97G & 0.44P), no. of secondary branches per plant (0.74G & 0.29P), number of primary branches (0.77G & 0.54P) and oil content (0.70G & 0.51P) at genotypic and phenotypic levels.